Scalable colloidal synthesis of Bi2Te2.7Se0.3plate-like particles give access to a high-performing n-type thermoelectric material for low temperature application - Chauhan, Nagendra S. (2020)
Colloidal synthesis is harnessed for the gram-scale preparation of hexagonal-shaped plate-like Bi2Te2.7Se0.3 particles, yielding nearly 5 g of the product in one experiment. The resultant textured particles are highly crystalline, phase-pure, chemically uniform, and can serve as a starting material for the preparation of bulk thermoelectrics for room temperature applications. The consolidation occurs via spark plasma sintering, which affords nanostructured n-type Bi2Te2.7Se0.3 material exhibiting a high figure of merit ZT ≈ 1 at 373 K with an average ZT ≈ 0.93 (300-473 K). Our experimental and theoretical studies indicate that the high thermoelectric performance is attributed to a favorable combination of the resultant transport properties. Specifically, bottom-up formation of the plate-like particles results in the substantial reduction of thermal conductivity by nanostructuring as observed experimentally and can be ascribed to phonon scattering at grain boundaries and suppressed bipolar conduction. When coupled with high electrical conductivity, which is preserved at the bulk scale as confirmed by ab initio calculations, these factors boost the thermoelectric performance of the as-synthesized n-type Bi2Te2.7Se0.3 bulk nanostructured alloy to the state-of-the-art level. The combination of a newly developed scalable colloidal synthesis with optimized spark plasma sintering constitutes a convenient route to nanostructured bulk thermoelectrics, which is an interesting pathway for the preparation of simple and complex thermoelectric chalcogenides.